Considerations for Evaluating Evolving Organizations and Initiatives - Lori Palen (The Evaluation Center at Western Michigan University, 2017)
Background: Evaluators are often called to be flexible in response to changing programmatic and contextual circumstances. However, the field offers little guidance around issues to consider before modifying an in-progress evaluation. Purpose: This article describes the evaluation of an organization that underwent significant mid-evaluation changes, with a focus on factors that went into the evaluator's recommendations about whether to modify evaluation design and instrumentation. Setting: Community collaborative in Wake County, North Carolina Intervention: NA Research Design: NA Data Collection and Analysis: The evaluator noted factors that went in to decisions about modifying evaluation design and instrumentation. Findings: Issues around validity and sustainability push evaluators to update our evaluation designs to keep pace with changes, whereas issues around continuity and accountability pull us to back to the current course.